PENGARUH FAKTOR LINGKUNGAN TERHADAP STRATEGI PEMASARAN DAN KINERJA PERUSAHAAN PADA INDUSTRI JASA KONSTRUKSI DI INDONESIA - Huda, Miftahul (Program Doktor Ilmu Ekonomi, 2009)
This research is aimed examining the effects of internal environment, industry environment, external environment, and their implications toward the marketing strategy and company performance at construction service industries in Indonesian. The objectives of this research are to prove and to analyze the effect of internal environment, industry environment, external environment variable toward marketing strategy and company performance of medium and small class at construction service industries in Indonesian.This research is a causality study. The data were collected by questionnaires. Populations of this study are all medium and small class at construction service industries in Indonesian. Data analyzed using the Structural Equation Modeling (SEM) with SmartPLS.The results of the research showed the following evidents:Internal environment variable has positive and significant effect on marketing strategy of medium and small class at construction service industries in Indonesian.Internal environment variable has positive and significant effect on company performance of medium and small class at construction service industries in Indonesian.Industry environment variable has not significant effect on marketing strategy of medium and small class at construction service industries in Indonesian.Industry environment variable has not significant effect on company performance of medium and small class at construction service industries in Indonesian.External environment variable has positive and significant effect on marketing strategy of medium and small class at construction service industries in Indonesian.Internal environment variable has not effect on company performance of medium and small class at construction service industries in Indonesian.Marketing strategy variable has positive and significant effect on company performance of medium and small class at construction service industries in Indonesian.There is has not different of marketing strategy between medium and small class at construction service industries in Indonesian, except marketing strategy that oriented at prime time and service flexibility.Â Keywords : internal environment, industry environment, external environment, marketing strategy, company performance, and construction service.